An autopsy case of neuronal intermediate filament inclusion disease with regard to immunophenotypic and topographical analysis of the neuronal inclusions. Issue 6 (19th June 2015) - Inoue, Kimiko; Fujimura, Harutoshi; Ueda, Kayo; Matsumura, Tsuyoshi; Itoh, Kyoko; Sakoda, Saburo
Abstract : We report an autopsy case of neuronal intermediate filament inclusion disease (NIFID), in which pyramidal motor dysfunction preceded cognitive disturbance for 3 years from the onset. A 41‐year‐old Japanese man presented progressive spastic tetraparesis followed by cognitive impairment. His neurological symptoms gradually deteriorated and he died of pneumonia 16 years from the onset. His brain showed severe generalized atrophy with enlargement of ventricles. The microscopic examination revealed severe neuronal loss with gliosis and sponginess predominantly in the fronto‐temporal cortices, caudate and putamen. Many hyaline conglomerate inclusions (HC) without immunoreactivity for 'fused in sarcoma' protein (FUS) and some granular and small round FUS‐immunoreactive (FUS‐ir) neuronal cytoplasmic inclusions (NCI) were observed in the remaining neurons. Some neurons with HC had small basophilic inclusions which showed positive FUS‐ir, attached to HC in the cytoplasm. Otherwise, FUS‐ir large compact inclusions (so‐called Pick‐like) were also observed but were scarce. In the cerebral cortex and the neostriatum, frequency of the inclusions was well correlated with neuronal loss. In the brainstem, neuronal loss was mild and FUS‐ir inclusions dominated. In the subthalamic nucleus and red nucleus, there was no HC but there were many FUS‐ir inclusions without neuronal loss. The above findings suggest that cytoplasmic mislocalization and aggregation of FUS appear at the early stage of the disease, and the FUS aggregate process may not be a direct precedent structure of HC.